2001
DOI: 10.1159/000051700
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Effective Treatment of Refractory Facial Lesions in Atopic Dermatitis Using Topical Tacrolimus following Corticosteroid Discontinuation

Abstract: Background: Topical corticosteroids are commonly applied in atopic dermatitis (AD) treatment. However, their chronic use may be associated with significant side effects at the application site. Skin atrophy and other undesirable effects are frequently seen after long-term corticosteroid treatment. In addition, when application of corticosteroids is discontinued, a rebound phenomenon in the facial lesions can occur within several days. Topical tacrolimus, an immunosuppressant currently used to prevent rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…It is also favorable for the treatment of the facial skin because its penetration decreases with the improvement of the inflammatory skin lesions, in contrast to corticosteroid which can penetrate even into normal facial skin [16]. Kawakami et al [8]reported that topical tacrolimus treatment was safe and effective in refractory facial AD following corticosteroid discontinuation. On the other hand, one has to be alert to bacterial and viral infections such as herpesvirus on the skin treated with tacrolimus because it is an immunosuppressive agent that interferes with cell-mediated immunity [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also favorable for the treatment of the facial skin because its penetration decreases with the improvement of the inflammatory skin lesions, in contrast to corticosteroid which can penetrate even into normal facial skin [16]. Kawakami et al [8]reported that topical tacrolimus treatment was safe and effective in refractory facial AD following corticosteroid discontinuation. On the other hand, one has to be alert to bacterial and viral infections such as herpesvirus on the skin treated with tacrolimus because it is an immunosuppressive agent that interferes with cell-mediated immunity [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epidermal and dermal atrophy, barrier dysfunction of the stratum corneum (SC) also occurs. Recently, topical tacrolimus ointment has been introduced as an effective treatment for the facial lesions of AD [6, 7, 8]. However, information about its short-term as well as long-term effects on normal human skin is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…in atopic dermatitis, abrupt discontinuation of the prolonged use of topical corticostreoids can result in exacerbation within several days. Recently, topical tacrolimus has been shown to be safe and effective in refractory facial lesions of atopic dermatitis following corticosteroid discontinuation [3]. Here we describe the efficacy of topical tacrolimus as an adjunct in 3 patients with various cutaneous manifestations of LE in the face.…”
Section: Introductionmentioning
confidence: 98%
“…However, relapse often occurs after discontinuation of prolonged use of topical corticosteroids [3, 4]. This relapse, defined as exacerbated AD sometimes associated with facial swelling, is referred to as a rebound phenomenon [3, 5]. The mechanism underlying the rebound phenomenon has remained unclear, and though some clinical studies have evaluated this phenomenon, there are only a few reports focusing on it.…”
Section: Introductionmentioning
confidence: 99%